Hair extensions need to be considered during preoperative assessment. Issue 12 (December 2019) - Manton, RN; Molina, A; Gavin, N; Hazari, A
Hair extensions are an increasingly common hairstyling practice. Others have demonstrated these devices can lead to hair and scalp injuries. We describe a recent case where such an injury was narrowly avoided in a patient undergoing a long surgical procedure. We suggest that preoperative assessment procedures need to be aware of such devices and provide advice to patients accordingly.